1979
DOI: 10.1017/s0033291700030749
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pharmacological basis for the chemotherapy of enuresis

Abstract: SynopsisEnuresis is a disorder of micturition occurring in the absence of an organic urinary tract lesion. To understand its possible causation, the mechanisms controlling micturition are described together with the possible sites of action of various anti-enuretic agents, particularly imipramine. It is concluded that further research into the central control of micturition is required before the precise actions of centrally-acting anti-enuretic agents can be elucidated. Knowledge of these may give insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Kales and Rapaport [57] have shown that the enuretic effects of imipramine appear to be independent of its effects on sleep stage. Imipramine also has a weak peripheral anticholinergic and antispasmodic effect as well as having an effect on the sympathetic nervous system input to the bladder [58]. The bladder capacity of enuretics was increased by 34% in one study, which supports this mechanism of imipramine action in enuretics.…”
Section: Pharmacotherapymentioning
confidence: 69%
“…Kales and Rapaport [57] have shown that the enuretic effects of imipramine appear to be independent of its effects on sleep stage. Imipramine also has a weak peripheral anticholinergic and antispasmodic effect as well as having an effect on the sympathetic nervous system input to the bladder [58]. The bladder capacity of enuretics was increased by 34% in one study, which supports this mechanism of imipramine action in enuretics.…”
Section: Pharmacotherapymentioning
confidence: 69%
“…Hunsballe et al [13] reported that the antidiuretic effect of imipramine can be attributed primarily to increased ·-adrenergic stimulation in the proximal tubules with a secondary increased urea and water re-absorption more distally in the nephron. A peripheral anticholinergic action and a blocking effect on amine of norepinephrine and serotonin re-uptake at sympathetic nerve terminals have been suggested as possible mechanisms for the anti-enuretic properties of imipramine [13,14]. Re-uptake inhibition leads to accumulation and increased availability of neurotransmitter substances at the postsynaptic membrane [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, tricyclic antidepressants were the drugs of choice for the treatment of enuresis, and imipramine was the most frequently prescribed drug treatment (Blackwell & Currah, 1973;Foxman et al, 1986;Stephenson, 1979). The mechanism by which imipramine reduces bedwetting is still, for the most part, unknown (Stephenson).…”
Section: Medications and Their Mechanisms Of Changementioning
confidence: 99%